2010
DOI: 10.1177/0032329209357888
|View full text |Cite
|
Sign up to set email alerts
|

Institutionalizing Dualism: Complementarities and Change in France and Germany

Abstract: The French and German political economies have been significantly reconfigured over the past two decades. Although the changes have often been more piecemeal than revolutionary, their cumulative effects are profound. The authors characterize the changes that have taken place as involving the institutionalization of new forms of dualism and argue that what gives contemporary developments a different character from the past is that dualism is now explicitly underwritten by state policy. They see this outcome as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
550
1
24

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 596 publications
(592 citation statements)
references
References 21 publications
17
550
1
24
Order By: Relevance
“…Liberal welfare states have been found to adapt more quickly, but in ways that exacerbate existing high levels of inequality. Such welfare policies can be identified in in the U.S.A. and United Kingdom in conservative welfare states, previously characterised as frozen landscapes [25], have also demonstrated adjustment, but at the cost of dualisation [26], which is also evident in Mediterranean welfare models. Dualisation in a society means that there are considerable amount of people (1) who are Boutside societyâ nd (2) who are defined to be Bunderclass^, (3) who have the status of Bworking poor^and (4) who are Bdis-advantaged^.…”
Section: European Welfare States In Transitionmentioning
confidence: 99%
“…Liberal welfare states have been found to adapt more quickly, but in ways that exacerbate existing high levels of inequality. Such welfare policies can be identified in in the U.S.A. and United Kingdom in conservative welfare states, previously characterised as frozen landscapes [25], have also demonstrated adjustment, but at the cost of dualisation [26], which is also evident in Mediterranean welfare models. Dualisation in a society means that there are considerable amount of people (1) who are Boutside societyâ nd (2) who are defined to be Bunderclass^, (3) who have the status of Bworking poor^and (4) who are Bdis-advantaged^.…”
Section: European Welfare States In Transitionmentioning
confidence: 99%
“…Our interest concerns those reform measures that are directed towards a more liberal labour market configuration and are often discussed as forms of activation (Palier, 2010;Gilbert, 2002;Palier and Thelen, 2010). This term refers to a wide range of institutional measures 1 -here, we focus on elements of activation policies that act as mechanisms to stimulate market forces and thereby produce risks on the individual level.…”
Section: Labour Market Reform Policies and Institutional Filtersmentioning
confidence: 99%
“…In recent decades, social and labour policy reforms have substantially changed the context of employment in advanced societies (Gilbert and Voorhuis, 2001;Palier, 2010). Empirical research has shown that this process led to increasing rates of atypical employment, lowwage work, and in-work poverty (Lohmann, 2009;Andreß and Lohmann, 2008;Lucifora et al, 2005;OECD, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, a new approach -the dualisation literature -has gained importance within the field of comparative political economy (Rueda, 2007;Palier and Thelen, 2010;Emmenegger et al, 2012). As can be seen below, each of these three strands of literature has different analytical roots and attempts to deal with different socio-political challenges.…”
Section: Explaining Growing Labour Market Inequalities Based On Agementioning
confidence: 99%
“…These authors have pinpointed the process of dualisation as the main driver of change (Rueda, 2007;Palier and Thelen, 2010;Emmenegger et al, 2012). Although these scholars speak of the existence of different patterns of dualisation (Schwander and Hausermann, 2013), they do not explain why in some countries it is mostly young labour market participants who are the outsiders.…”
Section: Introductionmentioning
confidence: 99%